MUTU GURU DALAM PERSPEKTIF MANAJEMEN STRATEGIK DI SEKOLAH DASAR - Erny Roesminingsih, (Pendidikan Dasar, 2010)
Abstract;  This research aims at developing a training model to improve the teacher quality to make them prepared to face  global competition. The specifications of the model comprises a) identification of organizational needs consisting of SWOT analysis, choice of strategy alternatives and strategy formula; b) needs analysis; c) training plan; d) training implementation; e) evaluation. After the tryout it shows that this model is proved to be  effective.